Analysis Effectiveness Of The Accounting Information System For Cash Receipts And Disbursements In Supporting Internal - Putri Nurpasya; Any Eliza; Ersi Sisdianto; A. Zuliansyah Zuliansyah; Adjila Mohamed (LP2M IAIN Palopo, 2024)
Internal control and Accounting Information System are closely related. In the cash receipts and disbursements cycle, the use of AIS is a necessity because there is a significant risk of misappropriation, thus requiring strict supervision of cash. Companies are expected to utilize AIS technology carefully to enhance effectiveness. The research aims to measure the effectiveness level of the Cash Receipts and Disbursements AIS in supporting internal control, which will be further examined from an Islamic perspective. This is a qualitative research where primary and secondary data are sourced from interviews and documentation. Data analysis is descriptive and qualitative, combined with a checklist method using Dean J. Champions' formula to measure the AIS effectiveness, which serves as the basis for evaluating whether the AIS can support internal control at PT. Haleyora Power Region 7 Lampung.The measurement results based on quality standards and Sharia principles show a score of 100%, and the evaluation indicates that the AIS has proven to be effective in supporting the internal control procedures at PT. Haleyora Power Region 7 Lampung.